2012
DOI: 10.1017/s0007114512004369
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary intake, glucose metabolism and sex hormones in women with polycystic ovary syndrome (PCOS) compared with women with non-PCOS-related infertility

Abstract: The present study investigated dietary intake, glucose metabolism and sex hormones in women with polycystic ovary syndrome (PCOS). A total of forty-five women (aged 25 -40 years) with PCOS and 161 control women (aged 25-43 years) with non-PCOS-related infertility were recruited. Anthropometry, glucose tolerance and sex hormones were determined and dietary intake was assessed. Women with PCOS had lower serum sex hormone-binding globulin and increased BMI, waist:hip ratio, luteinising hormone, ratio of luteinisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
1
23
1
1
Order By: Relevance
“…The PCOS participants in the current study reported consuming a higher proportion of energy from total dietary fat and SFA compared with controls, and exceeded the Department of Health guidelines . These findings are in agreement with previous studies in the UK, Taiwan and Iran . Although the findings do contradict those from Altieri et al .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The PCOS participants in the current study reported consuming a higher proportion of energy from total dietary fat and SFA compared with controls, and exceeded the Department of Health guidelines . These findings are in agreement with previous studies in the UK, Taiwan and Iran . Although the findings do contradict those from Altieri et al .…”
Section: Discussionsupporting
confidence: 90%
“…However, other authors have reported greater energy intakes by women with PCOS, 22,23 and Tsai et al reported lower energy intakes perhaps suggestive of differences in methodologies and underreporting. 24 The PCOS participants in the current study reported consuming a higher proportion of energy from total dietary fat and SFA compared with controls, and exceeded the Depart-ment of Health guidelines. 16 These findings are in agreement with previous studies in the UK, Taiwan and Iran.…”
Section: Discussionmentioning
confidence: 51%
“…reported an increased fat intake and a reduced fiber intake in patients with PCOS, which was related to weight differences between the groups. For Taiwanese women with PCOS, lower energy and carbohydrate intake and a higher fat intake have been reported . However, the body mass index was a confounding factor for these results.…”
Section: Discussionmentioning
confidence: 85%
“…Chlamydia and gonorrhea are most common STI which lead to infertility in men and women. Chlamydia is among the most common STI in England and 196 new cases affected with this infection were identified in 2011; youth (aged [15][16][17][18][19][20][21][22][23][24] were at risk of this disease more than others. This disease has no symptom.…”
Section: Endometriosismentioning
confidence: 99%
“…Articles show that nearly 10% of sub-fertile or infertile women have been diagnosed with diminished reduced ovarian (DOR) (23). Polycystic ovary is one of the common reasons of ovulation disorder in women of childbearing age (24). Some studies have shown that usually 30%-70% of women with PCOS are obese.…”
mentioning
confidence: 99%